2016
DOI: 10.17113/ftb.54.03.16.4346
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Phytochemical, Metal Contents and Antioxidant Activities of Black Glutinous Rice Bran and Potential Chemoprevention

Abstract: SummaryIn this work total anthocyanin content (TAC), total fl avonoid content (TFC), total phenolic content (TPC) and minerals found in fi ve black glutinous rice cultivars (MS, SK, PY, PC and KK) from Thailand were analyzed. The antioxidant activity of anthocyanin-rich black glutinous rice bran extracts against nitric oxide radical (NO˙), superoxide radical (O 2˙¯) and lipid peroxyl radical (LOO˙) was also determined. Potential chemopreventive property of rice bran extract was screened based on cellular bioas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…For success, relationships among traits such as grain yield, quality, nutrient content, and stress adaptation must be studied in detail. Previous research investigated the relationship between morphological traits and grain quality [27], between mineral elements and other quality traits [28,29], and between grain yield and physiological grain traits [30]. However, a full understanding of the possibility to produce high-yielding rice of good quality at stressful conditions, in particular drought, is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…For success, relationships among traits such as grain yield, quality, nutrient content, and stress adaptation must be studied in detail. Previous research investigated the relationship between morphological traits and grain quality [27], between mineral elements and other quality traits [28,29], and between grain yield and physiological grain traits [30]. However, a full understanding of the possibility to produce high-yielding rice of good quality at stressful conditions, in particular drought, is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between the TPC and TFC and antioxidant activity, including DPPH, NO and SO radical scavenging activity and FRAP activity of bark and wood were analysed (Tables 4 and 5). Specifically, a correlation coefficient of (r) > 0.6 shows extracts with strong antioxidant activity (57). Analysis of the strong correlation between the phenolic content and antioxidant activities showed that the TPC exhibits radical scavenging ability as follow; DPPH scavenging activity of H. cordifolia bark (r = 0.…”
Section: Correlation With Phytochemical Constituents and Ic50 Values Of Antioxidantmentioning
confidence: 99%
“…The correlation coefficient (r) was obtained from bivariate correlation analysis and used to describe the correlation between the antioxidant activity and the content of antioxidant components (TPC, TFC, TAC, Cu, Fe, Mn, and Zn). Three correlation levels were defined: strong (r=±0.600-1.000), moderate (r=±0.400-0.599), and weak (r=±0.000-0.399) 28 .…”
Section: Correlation Between Antioxidant Activity and Tpc Tfc Tac And Mineral Contentmentioning
confidence: 99%